Need Analysis for Local Wisdom and Ecoliteracy Based E-Story Book in Elementary Reading Comprehension - Perawati Perawati; Santi Oktarina; Erna Retna Safitri (AL-ISHLAH: Jurnal Pendidikan, 2025)
Reading comprehension is a foundational skill in elementary education, yet many students struggle due to limited access to engaging, relevant, and contextual learning materials. Traditional reading resources often lack cultural and environmental relevance, resulting in low student motivation. Integrating local wisdom and ecoliteracy into digital media offers a promising solution to enhance both literacy and character education. This study reports the analysis phase of a broader development project using the ADDIE model, focusing on the design of an e-story book that integrates local wisdom and ecoliteracy to support reading comprehension. The research employed a mixed-methods approach involving 26 fourth-grade students and 2 teachers from two public elementary schools in Ulak Embacang. Data were collected through validated questionnaires and interviews, then analyzed descriptively. Findings indicate a strong need for interactive and contextual digital reading materials. Both students and teachers rated learning objectives, narrative texts, and environmental themes as highly important. While multimedia formats such as PDF and animation were favored, tools like Kahoot and web-based platforms received lower interest. Students also reported limited access to varied reading resources and low engagement with conventional materials. The analysis underscores the urgency of developing culturally responsive and environmentally themed digital media. The proposed e-story book has the potential to improve reading comprehension while fostering ecological awareness and local cultural appreciation among students.